Pinning impulsive synchronization of complex-variable dynamical network - Wu, Zhaoyan; Liu, Danfeng; Ye, Qingling (Communications in nonlinear science & numerical simulation, 2015)
•Synchronization of complex-variable dynamical network is investigated.•Pinning combining with impulsive control scheme is adopted to achieve the goal.•Adaptive strategy is adopted to relax the restrictions on the impulsive intervals.•The proposed adaptive impulsive control scheme is universal to some extent.•A method for choosing the impulsive instants is provided. In this paper, pinning combining with impulsive control scheme is adopted to investigate the synchronization of complex-variable dynamical network. Based on the Lyapunov function method and mathematical analysis technique, sufficient conditions for achieving synchronization is first analytically derived. This result extends the condition derived for real-variable dynamical network to complex-variable network. Further, adaptive strategy is adopted to relax the restrictions on the impulsive intervals and reduce the control cost. Noticeably, the proposed adaptive pinning impulsive control scheme is universal for different dynamical networks to some extent. The impulsive instants are chosen by solving a series of maximum problems subject to the derived conditions. Several numerical simulations are performed to illustrate the effectiveness and correctness of the derived theoretical results.